2012
DOI: 10.3899/jrheum.110987
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Diagnostic Utility of Cardiac Magnetic Resonance Imaging, Computed Tomography, and Echocardiography in Assessment of Suspected Pulmonary Arterial Hypertension in Patients with Connective Tissue Disease

Abstract: In patients with CTD and suspected PAH, cardiac MRI and echocardiography have greater diagnostic utility than CT in the assessment of patients with suspected PAH, and MRI has prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 39 publications
2
77
2
3
Order By: Relevance
“…12 Although RVEF quantification with CMR avoids most geometric assumptions, its diagnostic value (based on AUC) was not statistically better than that of RVFAC in our study, possibly because difficulties in delineating the endocardial boarder of the RV base-to-apex contiguous slices might lead to RVEF measurement errors in some cases. 18 In previous studies, RVEF did not perform better than RVFAC to diagnose PH, and RVEF was not more strongly related to mPAP than was RVFAC, 12,13 as also observed in our study. Although we showed that RVFAC was clearly useful, measuring RVEF remains of critical importance in PH, as has been demonstrated by several different groups.…”
Section: Indices Of Rv Function Rv Dilation and Septum Bulgingsupporting
confidence: 80%
See 2 more Smart Citations
“…12 Although RVEF quantification with CMR avoids most geometric assumptions, its diagnostic value (based on AUC) was not statistically better than that of RVFAC in our study, possibly because difficulties in delineating the endocardial boarder of the RV base-to-apex contiguous slices might lead to RVEF measurement errors in some cases. 18 In previous studies, RVEF did not perform better than RVFAC to diagnose PH, and RVEF was not more strongly related to mPAP than was RVFAC, 12,13 as also observed in our study. Although we showed that RVFAC was clearly useful, measuring RVEF remains of critical importance in PH, as has been demonstrated by several different groups.…”
Section: Indices Of Rv Function Rv Dilation and Septum Bulgingsupporting
confidence: 80%
“…The present study demonstrated that the classic CMR indices of RV function, RV/LV interdependence, and PA function [8][9][10][11][12][13][14] showed essentially the same (good) value to rule in precapillary PH in treatment-naive subjects highly suspected to have pulmonary vascular disease. RVFAC 35% and the RVEDA/LVEDA ratio > 0.96 were especially valuable because of their high Youden index and high AUC.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A weak correlation between the main PA diameter and MPAP in connective tissue disease can be found [30], but appears to be mostly unaffected by the presence of ILD. For example, when Condliffe et al evaluated patients with limited systemic sclerosis, a weak correlation was found (r = 0.345, p = 0.002) between the main PA diameter and the MPAP, regardless of the extent of ILD [43].…”
Section: Correlation Between Pa Size and Phmentioning
confidence: 98%
“…Korábbi kutatások alapján a jobbszívfél-terhelés noninvazív megítélésére az echokardiográfi a és a szív MR képes jó szenzitivitás-sal, mögöttük elmarad a CT jelentősége. A mortalitás prognosztizálásában az MR-vizsgálatok nyújtották a legmegbízhatóbb eredményt (17). A rutinszerűen használható vizsgálómódszer a jobbkamra-funkció megíté-lésére mégis az echokardiográfi a. Ám a COPD-s betegpopuláció jobbkamra-funkciója kü lönösen nehezen megítélhető szívultrahang-vizsgá-lattal, több okból adódóan: elsősorban a betegség kö-vetkezményeként kialakuló emphysemás mellkas kö-vetkeztében kisebb akusztikus ablak kínálkozik a szív vizsgálatához, másodsorban a jobb kamra komplex geometriája miatt 2D-echokardiográfi ával direkt módon nem meghatározható az ejekciós frakció.…”
Section: Megbeszélésunclassified